Socializing Science Education Empowering Students Through the Use of Discourse and Argumentation of Socioscientific Issues - Wilkins, Christin (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Science teaching must begin to accommodate the changing role that science and technology has in the modern world. Citizens have increased avenues in which science can be used in decision-making in their lives and teaching students only content knowledge is not enough to equip them with the critical skills they need. Science education must promote social justice by giving all students opportunities to learn the nature of science as it relates to socio-scientific issues and explore the different values that are embedded in scientific decision-making. Science education should not only address content, it should encourage discourse and practice of science in order to empower students with skills to become responsible participants in their personal, professional and civic lives.